Assessment of Genetic Relationships between Growth Traits and Milk Yield in Egyptian Buffaloes - Ibrahim Abu El- Naser (Jurnal Ilmu Ternak dan Veteriner, 2019)
Data in this study were collected from live body weight records and milk yield for the first three lactations of Egyptian buffaloes maintained at the Mahallet Mousa Experimental Station of Animal Production Research Institute, relying on 987 records of Egyptian buffaloes spread over 16 years. These data were analyzed to estimate genetic parameters using animal model. Overall means in kilograms of BW, WW, W18, WFC, 1stMY, 2ndMY and 3rdMY were 36.56, 96.95, 322.02, 462.09, 1561.53, 1755 and 1837.71, respectively. Direct additive heritability (h2a) for mentioned traits were 0.31, 0.22, 0.24, 0.27, 0.23, 0.23 and 0.17, respectively. Corresponding computation of maternal heritability (h2m) for same traits were 0.39, 0.34, 0.22, 0.40, 0.29, 0.31 and 0.21, respectively. Evaluation of genetic correlations among different all studied traits were positive and ranged from 0.07 to 0.83, while phenotypic correlations were positive and ranged from 0.02 to 0.55. Accuracy of (PBV's) varying from 62 to 76, 62 to 83 and 41 to 77% for sires, cows and dams, successively; pointing out the genetic improvement could be achieved through any pathway of them. Higher direct and maternal heritability for BW and WFC and genetic correlations between first three lactations milk yield and each of BW and WFC higher than genetic correlations between first three lactations milk yield and WW and W18. Therefore, it is appropriate to select buffalo female calves for live body weight at birth than for live body weights at other ages.